Assessment of nephrotoxicity associated with combined cisplatin and mitomycin C usage in laparoscopic hyperthermic intraperitoneal chemotherapy. (1st January 2019) - Kapoor, Ravish; Robinson, Kristen Ashlee; Cata, Juan Pablo; Owusu-Agyemang, Pascal; Soliz, Jose Miguel; Hernandez, Michael; Mansfield, Paul; Badgwell, Brian
Abstract: Background : Laparoscopic hyperthermic intraperitoneal chemotherapy (HIPEC) has been used to treat various peritoneal malignancies. Cisplatin and mitomycin C (MMC) are agents commonly used in these procedures and, individually, each has been associated with acute kidney injury (AKI). There is limited literature on the complications associated with the use of both agents in HIPEC. Therefore, we sought to determine the incidence of nephrotoxicity and electrolyte abnormalities in patients undergoing laparoscopic HIPEC using this chemotherapeutic combination. Methods: We retrospectively evaluated patients undergoing laparoscopic HIPEC for gastric or gastroesophageal adenocarcinoma using both cisplatin and MMC. Sodium thiosulfate was given for renal protection and kidney function was evaluated daily up to postoperative day #2. Details regarding patient characteristics, selection criteria, chemotherapeutic regimen, perioperative lab values and anesthetic management were collected. Results: Twenty-three patients underwent 31 laparoscopic HIPEC procedures. Fifteen (65%) were male and the median age was 57 (range 21–75). Thirteen procedures were associated with an elevation in creatinine (Cr) with the median difference between POD#2 and baseline being 0.09 mg/dL (range 0–0.43). The glomerular filtration rate median difference between POD#2 and baseline was −17 mL/min/1.37 sq. m (range −42 to 11). No cases demonstrated AKI, defined as a 50% increase in Cr levels above baseline. An 84% incidence of postoperative hypophosphatemia (26/31) and 94% incidence of postoperative hypocalcemia (29/31) was observed. Conclusion: The laparoscopic approach to HIPEC using both cisplatin and MMC in our cohort was not associated with an increased incidence of AKI. The incidence of hypophosphatemia and hypocalcemia needs further evaluation to determine the exact etiology. Precis' statement: We retrospectively studied the association of AKI with the combined use of cisplatin and MMC in laparoscopic HIPEC.